Підвищення ефективності оптичного опромінювання в біотехнічних системах культиваційних споруд рослинництва - Червінський, Л. С.; Книжка, Т. С.; Романенко, О. І.; Луцак, Я. М. (Енергетика і автоматика, 2017)
INCREASING EFFICIENCY IN EXPOSURE OPTICAL SYSTEMS BIOTECH CROP CULTIVATION BUILDINGS L. Chervinsky, T. Knizhka, A. Romanenko, J. Lutsak Topicality. In the process of crop cultivation facilities of optical radiation is no alternative. It is the most important factor in photosynthesis, creating a climate for active plant growth and development. The positive effect of optical radiation is achieved through the ability of penetrating radiation and its specific effects on the cellular and molecular level in a biological object. Analysis of recent research and publications. Theoretical Foundations efficiency of optical radiation were examined VA Karpov, AA Kositsynym. They offered generalized mathematical model of the process of artificial irradiation power plants to quickly evaluate the effectiveness of and changes in the energy of this process for two main parameters - ’exposure intensity and duration of the exposure period Total. The aim – explore energy relative position of the radiation source and the irradiated surface and ground technological installation options alternating irradiation plant in cultivation facilities. Materials and methods. During the research methods used photometry, mathematical modeling and systems analysis. Results and discussion. Given the characteristics of receiving optical radiation power plants electrotechnological irradiation process can be represented by a number of energy conversion. The transformation of energy can be represented by a sequence of several stages: Stage 1 - supply of electricity from the source to the power plant; Stage 2 - flow generation optical radiation in the radiation source unit; Stage 3 - forming a stream of optical radiation in a given direction; Stage 4 - the formation of surface flow energy distribution beam on the surface of technological plants; Stage 5 - optical radiation energy absorption by the plant and its conversion into another form of energy. The biomass plant will be increased by creating efficient light irradiation treatment, which increases the efficiency of photosynthesis of plants. Irradiation in the test mode light installation created by moving irradiators speed mode and change the angle of the inclined work surface. Speed mode radiation sources form the alternating irradiation, which is characterized by the following parameters: duration of radiation sources (total time for which the plant receives artificial radiation throughout the vegetative period); normalized exposure (total exposure, which should get the plants for normal growth and development); speed irradiator sets the exposure (dose) exposure and duration of exposure to the plant. Conclusions and Prospects. Specific plant productivity depends on the increase in biomass plants. This requires a uniform irradiation of the surface by regulating the angle of the sloping surface. A radiator designed for specific areas of exposure if increasing the area, the productivity decreases. Variable exposure generated by moving reflectors increases the specific productivity of plants, but the limiting factor is the way to go one radiator. Thus, the optimized parameters Irradiation installations, namely speed and angle illuminators inclined surface. The criterion for optimization is the mass of dry matter plants as an indicator of the effectiveness of this technical solution.